تطور تسويق الخدمات القانونية والمشاكل التي تعترضها في الجمهورية العربية السورية - ديب, محمد ناصر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The legal services market must be properly viewed as a set of national markets constrained by a narrow national regulations that determine who can provide legal services within each jurisdiction as appropriate way. The research aims to study the development of the theoretical bases for marketing the legal services of the specific form and the use of marketing in the legal activity and create an effective lifting system for the marketing of the legal service and the achievement of regular ways to develop the marketing of legal service in the Syrian Arab Republic. The research is designed to solve all practical tasks and has a specific asset in meeting the recruitment and future development of the legal system in the country. يجب أن يُنظر إلى سوق الخدمات القانونية بشكل صحيح على أنه مجموعة من الأسواق الوطنية مقيدة بالأنظمة الوطنية الضيقة التي تحدد من يمكنه تقديم الخدمات القانونية داخل كل ولاية قضائية بالشكل المناسب. يهدف البحث إلى دراسة تطور الأسس النظرية لتسويق الخدامات القانونية للشكل المحدد واستخدام التسويق في النشاط القانوني و خلق نظام رفع ذو فاعلية لتسويق الخدمة القانونية وإنجاز الطرق المنتظمة لتطوير تسويق الخدمة القانونية في الجمهورية العربية السورية، كما أن البحث موجه لحل كل المهام العملية ويحمل في طياته رصيداً محدداً في تلبية التوظيف والتطور المستقبلي للنظام القانوني في البلد.